Prospects of Organic Conducting Polymer Modified Electrodes: Enzymosensors - Ravindra P. Singh (International Journal of Electrochemistry)
Organic conducting polymer modified electrodes (OCPMEs) have emerged as potential candidates for electrochemical biosensors due to their easy preparation methods along with unique properties, like stability in air and being compatible with biological molecules in a neutral aqueous solution. OCPMEs are playing an important role in the improvement of public health and environment for the detection of desired analytes with high sensitivity and specificity. In this paper, we highlight the prospects of OCMEs-based electrochemical enzymosensors.